2019
DOI: 10.1681/asn.2018050540
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1 Inhibitor–1 Mediates the cAMP-Dependent Stimulation of the Renal NaCl Cotransporter

Abstract: Background: A number of cAMP-elevating hormones stimulate phosphorylation (and hence activity) of the NaCl cotransporter (NCC) in the distal convoluted tubule (DCT). Evidence suggests that protein phosphatase 1 (PP1) and other protein phosphatases modulate NCC phosphorylation, but little is known about PP1's role and the mechanism regulating its function in the DCT. Methods: We used ex vivo mouse kidney preparations to test whether a DCT-enriched inhibitor of PP1, protein phosphatase 1 inhibitor-1 (I1), mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
3
31
1
Order By: Relevance
“…The role of PP1 was confirmed when the endogenous inhibitor of PP1, I-1, was deleted in mice, and pNCC levels decreased independent of total NCC abundance (242). Furthermore, PP1 interacts with NCC and can dephosphorylate it in vitro (239). The current view is that changes in cAMP, which can occur via, e.g., the ␤-adrenergic receptor or the vasopressin type 2 receptor (V2R), stimulates protein kinase A (PKA) to phosphorylate I-1, which inhibits PP1 and ultimately leads to an increase in pNCC.…”
Section: Regulation Of Ncc By Phosphatasesmentioning
confidence: 89%
“…The role of PP1 was confirmed when the endogenous inhibitor of PP1, I-1, was deleted in mice, and pNCC levels decreased independent of total NCC abundance (242). Furthermore, PP1 interacts with NCC and can dephosphorylate it in vitro (239). The current view is that changes in cAMP, which can occur via, e.g., the ␤-adrenergic receptor or the vasopressin type 2 receptor (V2R), stimulates protein kinase A (PKA) to phosphorylate I-1, which inhibits PP1 and ultimately leads to an increase in pNCC.…”
Section: Regulation Of Ncc By Phosphatasesmentioning
confidence: 89%
“…Activation of α1-adrenoceptors inhibits the suppression of NCC during high salt intake via a WNK/SPAK/ OxSR1-dependent signaling pathway in rat kidneys (Frame et al, 2019). Dephosphorylation of NCC by the protein phosphatase 1 can be inhibited through a protein kinase A-dependent activation of the protein phosphatase 1 inhibitor via β1-adrenergic receptor activation (Penton et al, 2019).…”
Section: Effects Of Renal Sympathetic Norepinephrine Release and Epitmentioning
confidence: 99%
“…In one of our earlier in vitro studies in Xenopus oocytes, NCC activity was found to be regulated by Protein phosphatase 4 (PP4) through its interaction with a conserved N‐terminal amino acid threonine 58 of NCC, and this regulation was independent of WNK4 regulated NCC trafficking to the membrane (Glover, Mercier Zuber, Figg, & O'Shaughnessy, ). More recently, signaling pathways independent of the WNK4/SPAK cascade have been shown to regulate NCC phosphorylation (and therefore its activity) in the DCT (Penton et al, ). In vitro studies showed that protein phosphatase 1 (PP1) dephosphorylates NCC whereas the PP1 inhibitor calyculin A had the opposite effect, and protein kinase A (PKA)‐dependent phosphorylation of the PP1 inhibitor 1 abolished the PP1‐mediated dephosphorylation of NCC in ex vivo mouse kidney preparations (Penton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, signaling pathways independent of the WNK4/SPAK cascade have been shown to regulate NCC phosphorylation (and therefore its activity) in the DCT (Penton et al, ). In vitro studies showed that protein phosphatase 1 (PP1) dephosphorylates NCC whereas the PP1 inhibitor calyculin A had the opposite effect, and protein kinase A (PKA)‐dependent phosphorylation of the PP1 inhibitor 1 abolished the PP1‐mediated dephosphorylation of NCC in ex vivo mouse kidney preparations (Penton et al, ). A comprehensive study of PP inhibitors in our cells has not been done to confirm if either PP1 or PP4 are important controllers of NCC dephosphorylation in our model HEK cells.…”
Section: Discussionmentioning
confidence: 99%